Impact of Passive Smoking on Low Birth Weight among Pregnant Women in Active Labor: Passive Smoking on Low Birth Weight among Women in Active Labor - Akhter, Ayesha; Hanif, Aasma; Jabbar, Shagufta; Humaira, Mariyam; Khan, Aneela; Rashid, Attyia; Ali, Rafia; Chaudhry, Muneera Azim (Pakistan Journal of Health Sciences, 2024)
Passive smoking during pregnancy, also called second-hand smoke exposure or environmental tobacco smoke, pretenses a substantial threat to fetal and maternal health. Objectives: To evaluate the association between passive smoking exposure and adverse birth outcomes in low birth weight in pregnant women. Methods: A case-control study was conducted at the Department of Obstetrics and Gynecology, Sughra Shafi Medical Complex, Narowal, from January 2024 to June 2024, involving 150 pregnant women presenting in active labour. Non-probability consecutive sampling techniques were used. Passive smoker’s women were assessed for adverse birth outcomes like low birth weight. Data were analyzed using SPSS-23.0. The chi-square test was used to calculate associations between exposure and outcomes. Odds ratios were calculated with 95% confidence intervals, with p≤0.05 considered statistically significant. Results: 56.7% of the study population was exposed to passive smoking, of which 48.7% delivered Low Birth Weight infants as compared to 25.3% preterm births. Passive Smoker women had significantly higher odds of preterm births (OR: 2.7, p<0.05) and low birth weight (OR: 2.08, p<0.05). Additional risk factors for low birth weight included abnormal BMI (OR: 2.79, p<0.05), multiparity (OR: 6.43, p<0.05), and maternal age over 30 years (OR: 5.7, p<0.05). Conclusions: It was concluded that a significant association between passive smoking and adverse birth outcomes was found, especially Low Birth Weight and preterm. The risks were markedly higher among women over age 30 years, those with multiparity and abnormal BMI. Results highlight the need for directed interventions to decrease passive smoking exposure in pregnant women.